The Judge's Considerations Regarding Evidence Of Handphones In The Crime Of Defamation On Social Media - Marisa Kurnianingsih; Muhammad Risal Fitrah Ramadhan; Arief Budiono (Universitas Muhammadiyah Bima, 2023)
Social life in Indonesia is experiencing progressive development from various aspects. Crimes or criminal acts committed by individuals or groups are currently growing along with the development of technology. One of the crimes that are often violated in the scope of social media is the criminal act of defamation, where this crime is carried out by destroying the good reputation of others by using the media in the form of a cellphone as the main item used. Based on this description, this study aims to determine the validity and considerations of judges regarding cell phone evidence in cases and to find out the views of Islamic Criminal Law regarding evidence as reinforcement in cases. By using normative research methods, it can be seen that cellphone evidence is very useful in providing judges' considerations in deciding cases, and in Islamic law itself Evidence has been arranged based on what is stated in the sources of Islamic law itself. Things that can be done so that law enforcement can work properly are rejuvenating the existing rule of law in the State of Indonesia, and making expert views in interpreting evidence in Islamic law as one of the references